Instructor's guide to accompany Harnessing Autodesk land desktop 2005 - Zimmerman, Phillip J. (Thomson Learning,Autodesk Press, 2005)
The Autodesk land desktop project and drafting environment, Basic data group-points, Line and Curve data, Parcels, Surfaces, Site and parcel volumes...